Prototype Waterwheel Hydro Generator - Muhammad Danish Irfan,; Muhammad Faqrulhadi,; Othman, Khairulnizam (Multidisciplinary Applied Research and Innovation, 2024)
Pests pose a major threat to agricultural crops, causing major economic losses and affecting global food security. The aim of the project is to develop effective pest management and control techniques, with a particular focus on the use of light traps to mitigate crop damage. However, ensuring the continuous power supply of these traps remains a challenge. In this study, we propose the integration of small hydropower systems into agriculture as a sustainable solution to the problem of powering light traps. Small hydroelectric plants use the energy of flowing water, such as streams or irrigation canals, to generate electricity. Installing a small hydroelectric system on a farm can create reliable renewable energy to run light traps. Additionally, small hydroelectric systems have proven to be cost-effective in the long run because of their relatively low operating costs compared to the recurring costs of other energy sources. The scalability and adaptability of small hydro systems make them suitable for different farm sizes and water resources, allowing them to be tailored to the specific needs of individual farms. However, successful implementation requires careful consideration of site-specific conditions, a feasibility assessment, and compliance with regulatory and environmental requirements. Proper system design and regular maintenance are essential to ensuring the optimum performance and durability of small hydro systems. In summary, the integration of micro-hydroelectric power generation systems into agriculture provides a sustainable and reliable power source for light traps and improves the efficiency of agricultural pest control. The solution offers advantages such as continuous power supply, environmental sustainability, cost efficiency, and scalability. By adopting mini hydro-powered light traps, farmers can effectively control pests, reduce crop losses, and contribute to sustainable agricultural practices.